Design Of A Decision Support System For Assessing Lecturer Performance At International Women's University Using The Balanced Scorecard Method - Umar Sidik Maulana; Djajasukma Tjahjadi (INFOKUM, 2022)
The objective of this study is to build a decision support system (Decision Support System) that can aid in the evaluation of lecturer performance at the International Women's University. This study employs the balanced scorecard method for analyzing system requirements, which is based on four perspectives: the customer perspective (institutional customers), the financial perspective (college financing profile), the internal process perspective (assessing and measuring lecturer performance), and the growth perspective (understanding and measuring lecturer productivity). These are the findings of this study: 1) Determining strategic objectives from the financial, customer, internal process, and learning and growth process perspectives, based on UWI Bandung's vision, purpose, and strategy. 2) Determine the measurements and weights for evaluating performance indicators in the form of Key Performance Indicators (KPI) that align with the vision, purpose, and strategy of UWI Bandung. 3) Analyze data requirements and related components by integrating current systems, which can be utilized to analyze decision support systems for evaluating lecturer performance.